2019
DOI: 10.1002/edn3.31
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an unrecorded population of Yamato salamander (Hynobius vandenburghi) by GIS and eDNA analysis

Abstract: Background Biodiversity loss is a serious environmental problem, and human activities might be primarily responsible for the marked decline in animal populations globally. Amphibians, in particular, have significantly decreased in number in recent decades. One example is the endangered Yamato salamander (Hynobius vandenburghi), which is distributed in Central Japan and has a very restricted distribution in Gifu Prefecture. Aims We aimed to discover new populations of H. vandenburghi using a combination of GIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…We used two qPCR assays for Siberian salamander eDNA in this study. One, which was newly designed, targeted the Cytb region, and the other targeted the 12S rRNA region (Sakai et al, 2019).…”
Section: Qpcr Detection Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…We used two qPCR assays for Siberian salamander eDNA in this study. One, which was newly designed, targeted the Cytb region, and the other targeted the 12S rRNA region (Sakai et al, 2019).…”
Section: Qpcr Detection Assaysmentioning
confidence: 99%
“…For 12S, we used an existing primer set (Sakai et al, 2019). This primer set was originally designed for Hynobius species, but an in silico test with Primer-Blast, confirmed that there is no substitution with the sequence of the Siberian salamander.…”
Section: Qpcr Detection Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular-based analysis on the local algal-bacterial relationship may contribute to a step forward clarification for such a subject. For example, the technique can search the algal and bacterial species that were not present in the target oceanic area before but have increased dramatically in recent years, which is somewhat similar to the study done by Sakai et al for the discovery of an unrecorded population of Yamato salamander (Hynobius vandenburghi) by GIS and eDNA analysis 34 . Therefore, beyond the HAB…”
Section: Discussionmentioning
confidence: 80%
“…Environmental DNA metagenomics analysis has helped in the study of entire communities (Handley et al, 2019;Nichols and Marko, 2019), specific taxonomic groups (Ostberg et al, 2019), rare/cryptic species (Sakai et al, 2019), vulnerable species (Hunter et al, 2018), and also invasive species (Hunter et al, 2015;Robinson et al, 2019) making it an ideal tool to work on distribution censuses of many taxa. Presence/absence measures are now possible but abundance measures are still not entirely achievable since correct estimations of abundance based on eDNA are not precise enough currently, due to primer sensitivity to target DNA, seasonal variation of eDNA and environmental factors that diminish the correlation between eDNA and abundance (Bylemans et al, 2019;Yates et al, 2019).…”
Section: Introductionmentioning
confidence: 99%